Late-Onset Focal Epilepsy: Electroclinical Features and Prognostic Role of Leukoaraiosis - Tartara, Elena; Micalizzi, Elisa; Scanziani, Sofia; Ballante, Elena; Paoletti, Matteo; Galimberti, Carlo Andrea (Frontiers in Neurology, 2022)
The aim of this study was to describe electroclinical and prognostic characteristics, and investigate the role of leukoaraiosis, in new-onset elderly focal epilepsy outpatients aged ≥ 60 years referred to a tertiary epilepsy center between 2005 and 31 December 2020. Among the 720 patients referred to the center, we retrospectively selected 162 consecutive outpatients with a first referral for recent-onset focal epilepsy of unknown cause (UC) or structural cause (SC), and collected clinical, standard-EEG (S-EEG), 24-hour ambulatory EEG (A-EEG), and neuroimaging data. We also analyzed seizure prognosis after titration of the first antiseizure medication (ASM). One hundred and four UC and 58 SC patients, followed up for 5.8 ± 5.3 years (mean ± SD), were included. Compared with the SC group, the UC patients showed a predominance of focal seizures with impaired awareness (51.9% of cases) and focal to bilateral tonic-clonic seizures during sleep (25%); conversely, the SC group more frequently had focal to bilateral tonic-clonic seizures during wakefulness (39.6%) and focal aware seizures (25.8%) (p<0.0001). Oral or gestural automatisms were prevalent in UC epilepsy (20.2% vs 6.9% in the SC group, p=0.04). In UC compared to SC patients, interictal epileptiform discharges showed a preferential temporal lobe localization (p=0.0007), low expression on S-EEG, and marked activation during deep NREM sleep (p=0.003). An overall good treatment response was found in the whole sample, with a probability of seizure freedom of 68.9% at 1 year. The cumulative probability of seizure freedom was significantly higher in the UC compared with the SC group (p<0.0001). The prognosis was worsened by leukoaraiosis (p=0.012). In late-onset focal epilepsy of unknown cause, electroclinical findings suggest a temporal lobe origin of the seizures. This group showed a better prognosis compared with structural epilepsy patients. Leukoaraiosis per se negatively impacted on seizure prognosis.